Nielsen’s Unrealised Opera Plans - Krabbe, Niels (Carl Nielsen Studies, 2020)
In addition to the two finished operas of Nielsen, scattered sources show that throughout his life he had at least five other opera projects in mind, which for various reasons were given up at different stages in their progress. The article presents the sources that are available for these projects, comprising the following works: Judith, Psycke, The Silent Woman, Portia, and Fru Marie Grubbe. The focus of the article is on Nielsen’s plan to compose an opera based on Shakespeare’s The Merchant of Venice under the working title Portia. Two important manuscripts in the Royal Library show that Nielsen himself had worked out a complete synopsis for the opera, and that the librettist, Sophus Michaëlis, had made a full text of the first act. A comparison of the two manuscripts and Shakespeare’s play reveals that the opera would have been quite different from the model with its focus on the character of Portia and the leaving out the merchant Antonio. Nielsen apparently gave up the idea, and no music from the work in progress worth mentioning is known.